Infrastructure Changes in Critical Care Unit to Prevent Multidrug-Resistance Organisms Spreading during COVID-19 Pandemic: the Effect on Clinical Outcomes and Cost Reduction in Chaopraya Abhai Bhubejhr Hospital, Prachinburi, Thailand - Dhamarak, Soraya; Pinsai, Subencha (Journal of Health Science of Thailand, 2023)
Increasing multidrug-resistant organisms (MDROs) is one of the public health concerns. There has been an increase in many MDROs during the pandemic of COVID-19. The objectives of this study were to compare MDROs infection after implementing multimodal prevention, including infrastructure changes and control measures; and compare mortality rate, antibiotic consumption, and cost during admission. The retrospective study was conducted in the medical COVID-19 ICU of Chaopraya Abhai Bhubejhr Hospital, Prachinburi, Thailand, from 1 June 2021 to 31 October 2022. The ICU was renovated by removing unnecessary medical equipment, the old contaminated ceiling, installing the glass partition, touchless sliding door, and ventilation controlled system. Strict hospital infection and prevention control policy was applied. We collected characteristics, outcomes, and cost per admission and analyzed them by IBM SPSS Statistics version 29.0. Altogether 988 participants were included in the study with a mean age of 55.2±19.6 years; and 54 (5.5%) underwent endotracheal intubation with mechanical ventilation. There were 66 (11.3%) participants in the before-renovation group, and 6 (1.5%) participants in the after-renovation group who got MDROs colonization. The carbapenem-resistant Acinetobacter baumannii was the most common pathogen, 62 out of 66 (93.3%) before and 5 out of 6 (83.3%) in the after-renovation group. Hospital mortality and mean length of stay were significantly higher in the before-renovation group. The mean cost per person per admission was significantly higher before the renovation group (137,564.4±141,019.7 versus 39830.3±39599.4 Thai baht, p<0.001). The overall cost reduction during the study was 25,312,625.7 Thai baht. In conclusion, renovating the infrastructure, together with a comprehensive approach that includes hand hygiene, isolation precautions, environmental cleaning, antibiotic stewardship, and staff education, can prevent the spread of MDROs in the ICU, resulting in reducing the incidence of MDROs in the ICU, reducing admission cost and improving patient outcomes.